Measurement of the branching fraction ratios R(D+) and R(D[ast]+) using muonic τ decays - Aaij, Roel; Bachmann, Sebastian; Carus, Leon; Caspary, Rowina; Celani, Sara; Cocha Toapaxi, Carlos; De Cian, Michel; Dittmann, Lucas; Esen, Sevda; Frau, Giulia; Glaser, Fabian; Günther, Paul André; et al. (Physical review letters, 2025)
The branching fraction ratios of ¯𝐵0→𝐷+⁢𝜏−⁢¯𝜈𝜏 and ¯𝐵0→𝐷*+⁢𝜏−⁢¯𝜈𝜏 decays are measured with respect to their muonic counterparts, using a data sample corresponding to an integrated luminosity of 2.0 fb−1 collected by the LHCb experiment in proton-proton collisions at √𝑠 =13 TeV. The reconstructed final states are formed by combining 𝐷+ mesons with 𝜏−→𝜇−⁢¯𝜈𝜇⁢𝜈𝜏 candidates, where the 𝐷+ is reconstructed via the 𝐷+ →𝐾−⁢𝜋+⁢𝜋+ decay. The results are 𝑅⁡(𝐷+)=0.249±0.043±0.047, 𝑅⁡(𝐷*+)=0.402±0.081±0.085, where the first uncertainties are statistical and the second systematic. The two measurements have a correlation coefficient of −0.39 and are compatible with the standard model.